2017
DOI: 10.1111/ajgw.12309
|View full text |Cite
|
Sign up to set email alerts
|

More hawthorn and less dried longan: the role of information and taste on red wine consumer preferences in China

Abstract: Background and Aims: This study uses sensory evaluation techniques to test the relative influence of country of origin, price and sensory attributes on consumer preferences in a new wine market. Methods and Results: Red wines from France, Australia and China were tasted by Chinese consumers under blind or informed conditions. Sensory descriptive data were collected from a Chinese-trained panel. A higher price and being from France were the strongest predictors of informed liking, while being from China had a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…These outcomes are similar to Lange et al (2002) who found no differences in liking among the Champagnes when tasted blind and clear differences in preference when the labels were shown, and to Williamson et al (2018) who revealed no significant differences in Chinese consumer hedonic liking among the 14 red wines evaluated under the blind condition. Nevertheless, further research should more precisely identify the sensory characteristics of different price-point wines and then investigate the relations among hedonic features and individual preferences.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These outcomes are similar to Lange et al (2002) who found no differences in liking among the Champagnes when tasted blind and clear differences in preference when the labels were shown, and to Williamson et al (2018) who revealed no significant differences in Chinese consumer hedonic liking among the 14 red wines evaluated under the blind condition. Nevertheless, further research should more precisely identify the sensory characteristics of different price-point wines and then investigate the relations among hedonic features and individual preferences.…”
Section: Discussionsupporting
confidence: 81%
“…Focusing specifically on wine extrinsic attributes, Sáenz-Navajas et al (2014) found that consumers’ knowledge, involvement and nationality appear to be good predictors of quality perception. In a recent study by Williamson et al (2018), the authors, focusing on the differences between liking scores in blind and informed condition, revealed that for Chinese consumers, the most influential attributes on informed liking (measured applying a nine-point hedonic scale), were price and country of origin.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in food culture have led to regional differences in preference for flavors or products. For example, Beijing consumers prefer characteristics described as fermented bean curd, spices/white pepper and bitterness in wine, whereas some characteristics associated with fruits, such as candy fruits, pear drop and tongue tingling, are preferred by Shanghai consumers …”
Section: Introductionmentioning
confidence: 99%
“…For example, Beijing consumers prefer characteristics described as fermented bean curd, spices/white pepper and bitterness in wine, whereas some characteristics associated with fruits, such as candy fruits, pear drop and tongue tingling, are preferred by Shanghai consumers. 20 Thus, it is critical to understand sensory perceptions, concepts and terms of regional target consumers to allow the identification of their sensory drivers of liking. External preference mapping, a technique that projects consumer liking onto the sensory space constructed with descriptive analysis, has been used repeatedly for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the recent studies on wine consumption have been performed in China, e.g. Balestrini and Gamble (2006), Liu and Murphy (2007), Somogyi et al (2011), Camillo (2012), Corsi, Marinelli, Sottini (2013, Agnoli, Capitello, and Begalli (2014), Liu et al (2014), Tang, Tchetchik and Cohen (2015), Williamson et al (2018), due to the attractiveness of the market in terms of size, and important advice on how to do research in wine marketing (Cohen and Lockshin, 2017). For example, Liu and Murphy (2007) indicate spirits are consumed for all occasions but special alcohol beverages, e.g.…”
Section: Studies In Asian Wine Marketsmentioning
confidence: 99%